DIFFERENT LEVELS OF SALICYLIC ACID AND DROUGHT IMPACTS ON MAIN PHYTOCHEMICAL COMPOUNDS OF SUNFLOWER (HELIANTHUS ANNUUS L.) - Hamad , Saber W.; Bapir, Shorsh H.; Salih, Sahar A.; Hussein, Rozhgar A.; Anwar, Talar K. (Science Journal of University of Zakho, 2024)
This study covered 2 locations, using 3 replications with randomized complete block design (RCBD) as a split-plot factorial arrangement, to determine the effect of both irrigation (I1, I2, & I3) and salicylic acid application (S1), and non-SA (S0) treatments, respectively, on sunflower seed oil % and main phytochemical components %, at ache-forming, flowering, and vegetative stages, compared to complete irrigation (I4). SA applied with full irrigation resulted in the highest values of seed oil % and overwhelming majority phytochemical components. On the contrary, the lowest values were noted by none (SA) application with skipping irrigation at the flowering-stage (I2S0).